A new proxy for investor sentiment: evidence from an emerging market. (2015) - Alrabadi, Dima Waleed Hanna
This study proposes order imbalance as a proxy for investor (market) sentiment. Using daily data from Amman Stock Exchange over the period (20042013), we find that the daily aggregate order imbalance measures and specifically the value of buyer-initiated shares less the value of seller initiated shares serves as an excellent proxy for investor sentiment. Thus, it shows a highly significant effect on the daily aggregate market returns even after controlling for the effects of lagged market returns and liquidity. Order imbalance proxies convey more information about market returns than trading activity measures. The Granger causality tests illustrate a bi-directional causality between investor sentiment and aggregate market returns.